What Can Biologic Aging Tell Us About the Effects of Mental Stress on Vascular Health - Sara, Jaskanwal Deep Singh; Lerman, Lilach O; Lerman, Amir (Hypertension (Dallas, Tex. 1979), 2023)
Cardiovascular disease is often a disease of aging. Considerable advances in our understanding of the biological mechanisms of aging have been made; yet, cardiovascular disease remains the leading cause of death in the United States urging a continued search for novel risk factors to target for preventing and treating disease. Mental stress (MS) is emerging as an important risk factor, and while progress has been made in understanding the link between MS and cardiovascular disease, the precise mechanisms of a putative causal relationship require greater clarification. In the current review, we (1) summarize our current understanding of the pathological effects of MS on vascular health; (2) describe important aspects of the pathobiology of vascular aging including inflammation, oxidative stress, mitochondrial dysfunction as well as novel processes such as genomic instability, epigenetic alterations, and nutrient signal pathways; (3) highlight similarities in the downstream biologic effects of aging and MS on vascular health with an emphasis on cellular and molecular processes that could be used to develop novel prognostic markers and treatment strategies for cardiovascular disease; (4) discuss lifestyle and pharmacological methods that target indicators of aging whose role could be translated into approaches managing the effects of MS; and (5) outline important future steps that should be considered in this area of research including the need for prospective clinical trials and for creating greater collaboration between preclinical aging researchers and clinical investigators managing MS.